2019
DOI: 10.1590/1679-78255089
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of bolted stiffened end-plate and bolted flange-plate connections

Abstract: This paper describes the experimental performance of the bolted stiffened end-plate (BSEP) and bolted flange-plate (BFP) connections using European hot-rolled profiles and built-up profiles. Four connections are designed and constructed according to FEMA-350 and are performed under cyclic loading. The influence of using different member profiles (European profiles and built-up profiles) in both the BSEP and BFP connections are examined. The obtained test results, including failure modes, hysteretic curves, ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
1
0
2
Order By: Relevance
“…Yilmaz dkk [8] melakukan analisis perbandingan sambungan extended end-plate (BSEP-01) dengan sambungan bolted flange plate (BFP-01) menggunakan profil baja eropa secara eksperimental. Detail konfigurasi spesimen sambungan dapat dilihat pada Gambar 3.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Yilmaz dkk [8] melakukan analisis perbandingan sambungan extended end-plate (BSEP-01) dengan sambungan bolted flange plate (BFP-01) menggunakan profil baja eropa secara eksperimental. Detail konfigurasi spesimen sambungan dapat dilihat pada Gambar 3.…”
Section: Pendahuluanunclassified
“…Hal ini dikarenakan tidak ada doubler plate atau ketebalan panel zone relatif tipis. Eksperimental yang dilakukan Yilmaz dkk [8] juga menunjukkan terjadinya pelelehan pada panel zone di akhir pengujian. Kapasitas momen dan rotasi yang dihasilkan oleh model numerik masing-masing sebesar 247,36 kN-m dan 4,83% dengan selisih antara model numerik dan eksperimental sebesar 4,05%.…”
Section: Simpulanunclassified
“…However, it also has a more complex connection with a steel beam than a square CFST column; this has limited the use of circular CFST columns; thus, they have relatively fewer joint forms. Seismic behavior tests of the core bolt and stiffened end-plate joints of square CFST columns and steel beams [9][10][11][12] have shown that these joints have excellent overall seismic performance, but the core bolts easily loosen under seismic loads and are prone to brittle failure when suddenly overloaded. Other studies [13][14][15][16][17][18] have shown that, because of the complex stress state of the bolt and steel tube when a similar joint is used for circular CFST columns and steel beams in seismic tests, the bolt breakage, pull-out, buckling, and tearing of the column wall easily occur under repeated seismic loads; this affects the restraint of the steel tube on concrete in the joint core area.…”
Section: Introductionmentioning
confidence: 99%